2018
DOI: 10.1007/s10822-018-0148-4
|View full text |Cite
|
Sign up to set email alerts
|

Protein–ligand pose and affinity prediction: Lessons from D3R Grand Challenge 3

Abstract: We report the performance of HADDOCK in the 2018 iteration of the Grand Challenge organised by the D3R consortium. Building on the findings of our participation in last year's challenge, we significantly improved our pose prediction protocol which resulted in a mean RMSD for the top scoring pose of 3.04 and 2.67 Å for the cross-docking and self-docking experiments respectively, which corresponds to an overall success rate of 63% and 71% when considering the top1 and top5 models respectively. This performance r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 27 publications
2
34
0
Order By: Relevance
“…This Table reports the statistics of the RMSD calculated on heavy atoms of each ligand after structural alignment on the reference conformation extracted from the experimental structure of the corresponding complex (hereafter indicated as RMSDlig-fit, to be distinguished from the same value calculated in the complex after alignment of the protein interface region). In all cases the minimum RMSDlig-fit values are lower than 2 Å, confirming the accuracy of the approach in reproducing near-native conformations [16]. Overall, these values are slightly larger than those obtained for the sampling of holo-like conformations of the receptor (2nd and 3rd columns in Table 3).…”
Section: Generation Of Near-native Ligand Conformerssupporting
confidence: 52%
See 2 more Smart Citations
“…This Table reports the statistics of the RMSD calculated on heavy atoms of each ligand after structural alignment on the reference conformation extracted from the experimental structure of the corresponding complex (hereafter indicated as RMSDlig-fit, to be distinguished from the same value calculated in the complex after alignment of the protein interface region). In all cases the minimum RMSDlig-fit values are lower than 2 Å, confirming the accuracy of the approach in reproducing near-native conformations [16]. Overall, these values are slightly larger than those obtained for the sampling of holo-like conformations of the receptor (2nd and 3rd columns in Table 3).…”
Section: Generation Of Near-native Ligand Conformerssupporting
confidence: 52%
“…In order to identify the putative binding site of the protein, we used the same approach presented in [16]. Namely, we retrieved in the PDB all the structures featuring at least 95% sequence identity to the amino acid sequence provided by the organizers and having a co-crystallized ligand (other than crystallization buffer molecules); this resulted in 340 entries.…”
Section: Binding Site Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…1,12,29,32−34 In particular, the inclusion of experimental structures of proteins bound to ligands similar to the one of interest has been shown to significantly increase the accuracy of docking. 5,8,12,32,35 Unfortunately, the number of targets whose three-dimensional (3D) structures have been experimentally solved remains limited compared with the druggable genome. 4,36 Furthermore, the exploration of different con-formations in experimental structures is generally limited and biased toward (often just a few) known ligand−receptor complexes, which impacts the chemical diversity of putative lead compounds in virtual screening campaigns.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The success of ensemble-docking is strongly dependent on the ability to include, in the pool of receptor structures, some conformation similar to the one found in the true complex 1,12,27,[31][32][33] . In particular, it has been shown that the inclusion of experimental structures of proteins bound to ligands similar to the one of interest significantly increased the accuracy of the method 5,8,12,31,34 . However, with reference to the druggable genome 35 , the number of targets whose three-dimensional structure has been experimentally solved remains still limited 4 .…”
Section: Introductionmentioning
confidence: 99%